(untitled) (Journal of Human Sciences, 2026)
This study examines the use of smartphones in English as a Foreign Language (EFL) classrooms among Libyan students at Sebha University, focusing on their attitudes, practices, and the challenges they encounter. The study adopted a mixed-methods research design, employing a quantitative questionnaire and qualitative semi-structured interviews. The participants consisted of 50 EFL undergraduate students from different semesters in the Department of English at Sebha University, who were randomly selected. The findings reveal that Libyan EFL students generally hold positive attitudes toward the use of smartphones in English language learning. Students reported noticeable improvement in their learning experiences due to the flexibility and accessibility that smartphones provide. They indicated that smartphones facilitate various learning practices, such as watching English videos, using dictionary and vocabulary applications, listening to audio materials, and engaging in online communication with teachers, all of which contribute to enhancing their English language skills. Despite these benefits, several challenges were identified, including distractions caused by social media, small screen sizes, and the high cost of internet access. However, most participants indicated that these challenges only slightly affected their learning process. Overall, the results suggest that smartphones can serve as an effective and valuable tool for EFL learning when accompanied by proper technological awareness, appropriate application selection, and strategies to minimize potential challenges. The study concludes with practical recommendations for EFL teachers on integrating smartphone use effectively in English language classrooms, particularly to support listening and speaking skills through audio-based activities.